PJMHS 2021
DOI: 10.53350/pjmhs2115103463
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Public Awareness About Clubfoot in The Al-Qassim Region and Importance of Early Childhood Intervention: A Cross-Sectional Study

Abstract: Background: Clubfoot is a childhood congenital abnormality that can lead to disabilities, which can last a lifetime if untreated. There are several types of interventions to treat this condition. However, these interventions depend on the age of presentation and result in good outcomes if started early. This study aimed to investigate the level of public awareness about clubfoot in the Al-Qassim region in Saudi Arabia. Method: This observational cross-sectional study was conducted on a population living in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…In addition, participants who said the best time for initial treatment of CTEV is from birth to six months tend to have a higher awareness level than others about CTEV (p-value=0.001). The previously mentioned associations were found to be consistent with the findings of the parallel study in which gender and having an affected child were found to be significantly associated with awareness about CTEV [19]. Age and marital status were not found to be significantly associated with awareness about CTEV.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, participants who said the best time for initial treatment of CTEV is from birth to six months tend to have a higher awareness level than others about CTEV (p-value=0.001). The previously mentioned associations were found to be consistent with the findings of the parallel study in which gender and having an affected child were found to be significantly associated with awareness about CTEV [19]. Age and marital status were not found to be significantly associated with awareness about CTEV.…”
Section: Discussionsupporting
confidence: 87%
“…The most reported source of information about CTEV was websites and the internet as stated by less than one-third (27%) of the participants followed by social media which was reported by (23.3%) of the participants, then relatives and friends as mentioned by (20.7%) of the participants and others and this was found to be similar to the findings of the congruent study except for that relatives and friends were the most reported source of information about CTEV followed by websites [19]. Physiotherapy was one of the most reported treatment options when asked about recovery rates for CTEV; however, 13.2% of participants reported recovery rates of 61%-80% after physiotherapy, while 54.2% are unaware of the exact recovery rates after physiotherapy.…”
Section: Discussionsupporting
confidence: 75%
“…Concerning medical history of the siblings the present study showed that, more than three quarter of the studied children had no siblings history. This may be due to less than two thirds of studied children were first ranking and there is a 10% chance of a subsequent child being affected if the parents already have a child with a clubfoot [25].This finding matches with [37] who conduct study about -The level of public awareness about clubfoot in the al-qassim region and importance of early childhood intervention: a crosssectional study‖ and found that majority of the studied children had no medical history of the siblings.…”
Section: Discussionsupporting
confidence: 68%